Quantification of microbial cells and virus-like particles in sediments from Atacama Trench - Clemens Schauberger; Mathias Middelboe; Ronnie N Glud (PANGAEA, 2024)
Sediment cores were collected using a multicorer (MUC). Microbes and virus-like particles were extracted from sediments in a 3°C room using a modified version of the washing protocol of Danovaro and Middelboe, 2010 (see Schauberger et al., 2021). After the washing procedure, the extracted microbial cells and virus-like particles were fixed with 25% glutaraldehyde (1% final concentration) and stored at -80°C prior to flow cytometry. These samples were measured in triplicates using a BD FACSCanto™ II flow cytometer, after staining with SYBR Green I. Sediment extracts were diluted 1 : 10 in 0.020.167emμm-filtered TE Buffer prior to all measurements. The flow rate was 5–7 μl/min, as determined by BD Trucount™ Beads. The laser settings and gating examples can be found in the Supporting Information of Schauberger et al. (2021).